Role of Hypoxia Induced by Medicinal Plants; A Revolutionary Era of Cellular and Molecular Herbal Medicine in Neuroblastoma Treatment - Samin Rahimi; Fatemeh Shirin; Mahdi Moassesfar; Hossein Zafari; Nazila Bahmaie; Kimia Baghebani; Yasna Bidmeshki; Seyede Masoumeh Sajjadi Manesh; Kasra Rasoulzadeh Darabad; Massoud Bahmaie; Elham Nouri; Ahmet Kilic; et al. (Frontiers in Bioscience-Landmark)
As one of the most common solid pediatric cancers, Neuroblastoma (NBL) accounts for 15% of all of the cancer-related mortalities in infants with increasing incidence all around the world. Despite current therapeutic approaches for NBL (radiotherapies, surgeries, and chemotherapies), these approaches could not be beneficial for all of patients with NBL due to their low effectiveness, and some severe side effects. These challenges lead basic medical scientists and clinical specialists toward an optimal medical interventions for clinical management of NBL. Regardingly, taking molecular and cellular immunopathophysiology involved in the hypoxic microenvironment of NBL into account, it can practically be a contributing approach in the development of “molecular medicine” for treatment of NBL. Interestingly, pivotal roles of “herbal medicine” in the hypoxic microenvironment of NBL have been extensively interrogated for treating a NBL, functionally being served as an anti-cancer agent via inducing a wide range of molecular and cellular signaling, like apoptosis, cell cycle arrest, and inhibiting angiogenesis. Hence, in this review study, the authors aim to summarize the anti-tumor effects of some medicinal plants and their phytoconstituents through molecular immunopathophysiological mechanisms involved in the hypoxic microenvironment of NBL. In addition, they try to open promising windows to immune gene-based therapies for NBL “precision medicine” through clinical advantages of herbal and molecular medicine. An interdisciplinary collaboration among translation and molecular medicine specialists, immunobiologists, herbal medicine specialists, and pediatric neuro-oncologists is highly recommended.